Annotated checklist of Hydraenidae (Coleoptera, Polyphaga) of Brazil - Benetti, Cesar J.; Hamada, Neusa (Zootaxa, 2022)
A checklist of known species of the water beetle Hydraenidae (minute moss beetles) recorded from Brazil is assembled, rendering a total of 34 species distributed in four genera: Adelphydraena Perkins, 1989 (one species), Hydraena Kugelann, 1794 (19 species), Parhydraenida J. Balfour-Browne, 1975 (11 species) and Ochthebius Leach, 1815 (three species). For each taxon a complete account of its nomenclature, including synonyms and historical name combinations are included. The habitats (when known) and geographical distribution of each species organized by Brazilian states are also provided.